Bogor City Government’s Communication Crisis in Handling Covid-19 - Tri Isniarti Putri; Djuara Pangihutan Lubis; Heri Budianto (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
The massive transmission of Covid-19 has spread in various regions, causing negative trends in various aspects of life. Bogor, West Java, which recorded 1,484 cases  is one of the areas that has  high Covid-19 transmission rate.  In addition, the Bogor City Government as a stakeholder has a large responsibility for overcoming a crisis in the midst of  uncertain situation. This study aims to analyze the development of the Covid-19 crisis communication message in the Bogor city government. This research method uses a qualitative descriptive approach. The data collection is conducted  through interviews, observation and documentation through photos and videos of the COVID-19 Task Force, government regulations and other sources. Based on the crisis emergency risk communication (CERC) model used by the researcher, the results show that the crisis communication process carried out by the Bogor City Government affects five phases, including: Pre-crisis, initial occurrence, maintenance, resolution, and evaluation, each of which has its own application and different handling such as in the pre-crisis phase, the Bogor  City Government presented a crisis message and formed a crisis team as part of preparation to deal with a crisis, the period of initial events, information in terms of meeting the public’s  needs for accurate, timely, credible, and consistent information. Then the stage of maintaining the form of communication is more tangible in the form of action, while the stage of creating new efforts to deal with new risks and the final evaluation, assessing the programs that have been run to get new innovations.